If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1g + s + -2g + 3(g + -2) = p Reorder the terms: 1 + -1g + s + -2g + 3(-2 + g) = p 1 + -1g + s + -2g + (-2 * 3 + g * 3) = p 1 + -1g + s + -2g + (-6 + 3g) = p Reorder the terms: 1 + -6 + -1g + -2g + 3g + s = p Combine like terms: 1 + -6 = -5 -5 + -1g + -2g + 3g + s = p Combine like terms: -1g + -2g = -3g -5 + -3g + 3g + s = p Combine like terms: -3g + 3g = 0 -5 + 0 + s = p -5 + s = p Solving -5 + s = p Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + s = 5 + p Combine like terms: -5 + 5 = 0 0 + s = 5 + p s = 5 + p Simplifying s = 5 + p
| 16t^2-80t-64=0 | | 3+9(-7+4s)= | | y=2(6) | | -56/-7/8 | | p--2=9 | | -5k+10k=0 | | g(x)=4.9t^2+6t+0.4 | | Log(1/2x) | | -20x+10=6+12x | | -3/4x-2=-8] | | -3(-7+2y)-6= | | -38x+7=159 | | (-9ln(x)-6)/(x^2)=0 | | 10=2x(8)+b | | 12s-s=22 | | -32x=-4 | | 3x=(x*x)-40 | | 18/6d-9=1/6 | | p=2k-2w | | 3X+5X-8=15-X | | Y^2+6Y=-20x-89 | | 9x+17(x+1)=17-4x | | X+7=-4x+2 | | -3n+4=n-3n | | 8.5w=-119 | | (2x-y+5z)(2x-y-5z)= | | 9x+(x+1)=17-4x | | 4w-6=11 | | 7y+5x=148 | | (x-6)/4 | | (k-2)x^2-5x+2=0 | | 5(-3-2m)+7m= |